2016
DOI: 10.1080/21505594.2015.1131381
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy postpones apoptotic cell death in PRRSV infection through Bad-Beclin1 interaction

Abstract: Autophagy and apoptosis play significant roles in PRRSV infection and replication. However, the interaction between these 2 processes in PRRSV replication is still far from been completely understood. In our studies, the exposure of MARC-145 cells to PRRSV confirmed the activation of autophagy and subsequent induction of apoptosis. The inhibition of autophagy by 3-methyladenine (3-MA) caused a significant increase in PRRSV-induced apoptosis, showing a potential connection between both mechanisms. Moreover, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…For instance, influenza A virus was documented to induce apoptosis in autophagy protein deficient cells [47]. Autophagy was also reported to postpone apoptotic cell death during porcine reproductive and respiratory syndrome virus (PRRSV) infection through Bad-Beclin1 interaction [48,49]. The interplay of autophagy and apoptosis during PEDV infection needs to be further elucidated for a better understanding of the autophagy mechanism by which PEDV benefits its infection.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, influenza A virus was documented to induce apoptosis in autophagy protein deficient cells [47]. Autophagy was also reported to postpone apoptotic cell death during porcine reproductive and respiratory syndrome virus (PRRSV) infection through Bad-Beclin1 interaction [48,49]. The interplay of autophagy and apoptosis during PEDV infection needs to be further elucidated for a better understanding of the autophagy mechanism by which PEDV benefits its infection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Benveunto et al has shown that SARS-CoV-2 induced mutations within the NSP6 protein, which in turn induced autophagosome formation by inhibiting phagosome-lysosome fusion ( 28 , 29 ). SARS-CoV-2 may take advantage of this autophagy mechanism, as the acidic pH required for endosome maturation also functions to release the virion at the appropriate site.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Recently, three additional research articles provided evidences that autophagy but also apoptosis are induced by PRRSV in host cells [ 61 , 62 , 64 ]. Wang and collaborators investigated apoptosis and autophagy activation in the thymus of piglets infected with the HP PRRSV strain because they previously showed that this virus leads to thymic atrophy and thymocyte apoptosis [ 61 ].…”
Section: Nidovirales and Autophagymentioning
confidence: 99%